On dialouge/ edited by Lee Nichol - "Bohm, David" (London, 2007)
Creativity is fundamental to human experience. In On Creativity David Bohm, the world-renowned scientist, investigates the phenomenon from all sides: not only the creativity of invention and of imagination but also that of perception and of discovery. This is a remarkable and life-affirming book by one of the most far-sighted thinkers of modern times.
Keywords: Philosophy of mind